The Role of Coordination Mechanisms Between the central Government and Local Administration Units In Improving the Performance of the Local Administration Bodies in Egypt - El-Gamal, Ayman Ahmed; Ismail, Mamdouh Mostafa; El Bagoury, Ayman Amin (The Arab Journal of Administration, 2025)
Purpose: Coordination between the central government and local administration is important to achieve complementarity of performance, prevent inconsistencies and overlap in the competencies between them, but it needs to develop mechanisms for coordination between them.Therefore, The paper aims to study the impact of coordination mechanisms between the central government and local units on the performance of local administration bodies in Egypt. Design/Methodology: the study used the analytical descriptive approach to analysis of coordination mechanisms between the central government and local units, as well as the legal approach based on the analysis of legal sources, many documents and data related to the coordination mechanisms to answer the study questions. Findings:The researcher intends to pinpoint coordination obstacles between the central government and Local authorities to develop the organizational relationships and patterns of interaction between the central government and Local authoritiesn and creating mechanisms for effective coordination between them and provide practical solutions for improving the performance of local administration bodies and present a roadmap for reform The local system in Egypt. Practical implications: the study is expected to be beneficial to decision makers with regard to using coordination mechanisms between the central government and Local authorities as a managerial approach to reform the local system in Egypt. Authenticity/value: the current study is the first published attempt to verify the role Coordination Mechanisms Between the central government and Local authorities in improving the performance of the local administration bodies in Egypt